Prevalence, Severity, and Self-Medication for Dysmenorrhea among Female Adolescents in Indonesia - Handika Zulimartin; Achmad Kemal Harzif; Amalia Shadrina; Juliana Sari Harahap; Anton Tanjung; R. Muharam (Majalah Kedokteran Bandung, 2025)
Dysmenorrhea, commonly referred to as menstrual pain, is a prevalent condition affecting many reproductive-aged women, particularly female adolescents, with varying degrees of intensity. Dysmenorrhea affects 64.5% of female adolescents in Indonesia, with the highest prevalence rates found in West Java (98.8%) and Jakarta (87.5%). Over the years, various therapy modalities have been developed for treating this condition based on its pathophysiology. However, in Indonesia, a country renowned for its rich natural resources and medicinal herbs, there is a prevailing belief in the efficacy of traditional medicine. Female adolescents in Indonesia are often engaged in self-medication practices, combining traditional medicine with nonsteroidal anti-inflammatory drugs (NSAIDs). This study aimed to analyze the prevalence, severity, and self- medication practices for dysmenorrhea among female adolescents in Indonesia. The study was conducted from January to December 2020 using an online survey that included questions about menstrual pain, family history, and the use of traditional medicine and NSAIDs. This study comprised 362 participants recruited through convenience sampling. Results showed that 92.5% of participants experienced dysmenorrhea with varying degrees of pain. A total of 216 (59.9%) female adolescents experienced frequent dysmenorrhea, while 118 (32.6%) reported experiencing this condition every menstrual cycle. Of all participants, 33.1% used traditional medicine as a treatment option, and 16.9% used NSAIDs. According to the self-reported visual analog scale (VAS), the use of natural remedies, such as traditional medicine, was associated with lower pain levels, suggesting their potential benefits in healthcare services for dysmenorrhea.